TCR β chain–directed bispecific antibodies for the treatment of T cell cancers - Paul, Suman (Sci Transl Med, 2021)
Immunotherapies such as chimeric antigen receptor (CAR) T cells and bispecific antibodies redirect healthy T cells to kill cancer cells expressing the target antigen. The pan-B cell antigen–targeting immunotherapies have been remarkably successful in treating B cell malignancies. Such therapies also result in the near-complete loss of healthy B cells, but this depletion is well tolerated by patients. Although analogous targeting of pan-T cell markers could, in theory, help control T cell cancers, the concomitant healthy T cell depletion would result in severe and unacceptable immunosuppression. Thus, therapies directed against T cell cancers require more selective targeting. Here, we describe an approach to target T cell cancers through T cell receptor (TCR) antigens. Each T cell, normal or malignant, expresses a unique TCR β chain generated from 1 of 30 TCR β chain variable gene families (TRBV1 to TRBV30). We hypothesized that bispecific antibodies targeting a single TRBV family member expressed in malignant T cells could promote killing of these cancer cells, while preserving healthy T cells that express any of the other 29 possible TRBV family members. We addressed this hypothesis by demonstrating that bispecific antibodies targeting TRBV5–5 (α-V5) or TRBV12 (α-V12) specifically lyse relevant malignant T cell lines and patient-derived T cell leukemias in vitro. Treatment with these antibodies also resulted in major tumor regressions in mouse models of human T cell cancers. This approach provides an off-the-shelf, T cell cancer selective targeting approach that preserves enough healthy T cells to maintain cellular immunity.